ANALISIS GAYA BAHASA PADA PUISI â€œKUBACA BISAâ€ KARYA ABDUL WACHID - Dandi Permana; Mimin Sahmini; Rochmat Tri Sudrajat (IKIP Siliwangi, 2021)
This research is entitled Analysis of Poetry entitled â€œKubaca Bisaâ€ by Abdul Wachid. This research is a form of contribution to the scientific development of Indonesian Language and Literature in analyzing poetry. This study aims to describe and interpret the language style used in the poem entitled